Effect of Vermiwash and Vermicompost on Soil Parameters and Productivity of Okra (Abelmoschus esculentus) in Guyana - Ansari, Abdullah Adil; Sukhraj, Kumar (African journal of agricultural research, 2010)
Present investigations were carried out during the year 2006 - 2007 at University of Guyana, Georgetown focusing on recycling organic waste using vermitechnology and use of vermicompost and vermiwash obtained from the vermitech in varied combinations for exploring the effect on soil and productivity of Okro (Abelmoschus esculentus) in Guyana. The soil quality was monitored during the experiment along with plant growth parameters of Okra. Findings are reported.